DIF in the Spanish Version of the Verbal Selective Reminding Test Using Samples From Hispanics in the United States, Mexicans, and Spaniards - Morales-Ortiz, Manuel; Peña-Cardenas, Fabiola (Frontiers in Psychology, 2019)
Before a test can be used in the target population, it is necessary to demonstrate that there is measurement equivalence. One way to do this is by studying differential item functioning. Objective: In this study, we used the Mantel-Haenszel procedure and logistic regression to analyze DIF in the Spanish version of the Verbal Selective Reminding Test between Spaniards, Mexicans and Hispanics in the United States. Method: Three balanced samples, matched by age, education and sex, were studied: Spaniards, Mexicans and Hispanics (616 healthy participants from Spain (n = 211), Mexico (n = 201) and the United States (n = 205). A six-trial version of the Spanish version of the Verbal Selective Reminding Test was administered and scored according to standard procedures. Results: Statistical analysis showed some differential item functioning between the samples of Spaniards, Mexicans and Hispanics. Bootstrap validation of results confirmed that the item pollo showed differential item functioning: the Mexicans and Hispanics outperformed the Spaniards, holding total score constant. The item oído also showed differential item functioning and was remembered in greater measure by the Spaniards. Conclusion: The Spanish version of the Verbal Selective Reminding Test can be used with Hispanic populations.